Recyclable Xanthan/TiO2 Composite Cryogels towards the Photodegradation of Cr(VI) Ions and Methylene Blue Dye - Paulo V. O. Toledo; Leandro R. Marques; Denise F. S. Petri (International Journal of Polymer Science)
Composite cryogels were prepared from xanthan gum (XG) precursor gels at 20 g L-1 containing TiO2 load at 5, 10, and 20 wt% and citric acid, as crosslinker. The effect of the pH over precursor gel on the properties of the resulting cryogels was evaluated. The characterization of the XG/TiO2 cryogels comprised compression tests, swelling degree (SD) determination, Fourier transform infrared vibrational spectroscopy in the attenuated total reflectance mode (FTIR-ATR), scanning electron microscopy (SEM), and X-ray microtomography (CT) analyses. The largest compressive modulus (E) was observed for XG/TiO2 10% cryogels prepared at pH 4.0, which amounted to 100±7 kPa, whereas the E value determined for bare XG cryogels was 29±3 kPa. XG/TiO2 10% cryogels presented larger pores and thicker walls than bare XG cryogels, as evidenced by SEM and CT analyses. FTIR-ATR spectra evidenced the ester bonds stemming from the esterification among carboxylic acid groups and/or XG hydroxyl groups. XG/TiO2 10% cryogels presented SD of (61±2) gwater/gcryogel, long-term stability in water, and outstanding photocatalytic properties in the presence of Cr(VI) ions and methylene blue (MB). The photocatalytic processes for the reduction of Cr(VI) to Cr(III) and for the photobleaching of MB fitted the first-order kinetic model, yielding rate constants of 0.019 varying min-1 and 0.0096 min-1, respectively. For both processes, the XG/TiO2 10% cryogels could be recycled five times without losing shape or efficiency.